Transcription as a Key Phase of Data Analysis in Qualitative Research: Experience from KwaZulu-Natal, South Africa. Issue 4 (November 2021) - Oluwafemi, Adeagbo; Xulu, S.; Dlamini, N.; Luthuli, M.; Mhlongo, T.; Herbst, C.; Shahmanesh, M.; Seeley, J.
Transforming spoken words into written text in qualitative research is a vital step in familiarizing and immersing oneself in the data. We share a three-step approach of how data transcription facilitated an interpretative act of analysis in a study using qualitative data collection methods on the barriers and facilitators of HIV testing and treatment in KwaZulu-Natal, South Africa.